Proses Penyelesaian Sengketa Hak Atas Tanah Yang Dijadikan Sebagai Jaminan Kredit Di Bank(Studi Kasus Pengadilan Negeri Surakarta) - RICHO, Richo, Nuswardhani, S.H., S.U, Darsono, S.H., MH (2015)
Credit or loan is providing money or resources based on agreement of borrowing and lending loan between banks and other parties which obligates the debtor to reimburse bank on a certain period of time with interest. In order to free the bank from any risk as the creditor, bank has always asked some warranty to secure the debt of the debtor. Bank asks the prospective debtor to mortgage their property, usually land title is used as warranty for the loan. In reality, the reimbursement from debtor is stopped in the middle, so the creditor and debtor had a falling-out related to that mortgage. This research uses descriptive normative method. Using secondary data and primary data. Literature studies, field studies and interviews are used as the techniques to collect the data. And with qualitative data analysis method. Based on the results of research and discussion the conclusion is, in order to settle down the dispute on any loans, there are two alternative ways, through non-litigation (negotiation) and through litigation (judicial). Through Non-litigation settlement, the bank can do some counter measures such as: (1) Rescheduling (New Schedule), (2) Reconditioning (Giving a new requirements), (3) Restructuring (Arrangement Again). The other way, litigation is to utilize the existing judiciary, both the District Court, the Commercial Court, or the State Receivables Affairs Committee (PUPN).